Intestinal occlusion caused by intussusception in an adult subject: Report of a case - Zevallos-Delgado, Gean (2023)
Intussusception as a cause of intestinal obstruction in adults is a very rare entity, the majority is secondary to a benign or malignant neoplasm of the small intestine. Lipomas are rare benign tumors, considered neoplasms of mature adipose tissue without pleomorphism that are found in the gastrointestinal tract as well-demarcated tumors of the submucosa, and are most often found within the wall of the small intestine. We present the case of a 72-year-old man who underwent surgery for intestinal obstruction, and an intraoperative diagnosis of small bowel intussusception secondary to a submucosal angiolipoma according to pathology. Intussusception in adults is rare, and the fact that it is due to another unusual benign entity is even rarer. Tomographic study is useful, but most are diagnosed intraoperatively. The resection "in block", is the most recommended due to the suspicion of malignancy.